Bioecological Characteristics of Cuminum Cyminum L. under Introductory Conditions - Solexovna, Tursunova Saida; qizi, Halimova Shoxina Eminjon (American Journal of Biology and Natural Sciences, 2025)
In recent years, numerous studies have been conducted in the field of chemistry. In this article, we will examine the cumin plant. This work analyzes the bioecological characteristics of Cuminum cyminum L. (cumin). The cumin plant is widely distributed in Central Asia and other regions, and there is a significant amount of scientific information regarding its use and role in ecosystems. The study investigates factors affecting the growth and development of cumin in ecological and agronomic conditions, including soil and climatic factors, the plant’s vegetation period, seed production processes, and other bioecological characteristics. The findings of this study are crucial for the effective and sustainable cultivation of cumin, providing important insights for agricultural producers in the field of agronomy.